Strategi Adaptasi Petani Padi Lahan Basah (Suboptimal) Pada Era Pandemi Covid -19 Di Kelurahan Keramasan Kecamatan Kertapati Kota Palembang Provinsi Sumatera Selatan - Arbi, Muhammad; Junaidi, Yulian; Januarti, Indri (Jurnal Social Economic of Agriculture, 2021)
The purpose of this study was to explore the socio-economic conditions of the community and analyze the adaptation strategies carried out by rice farmer households in the era of the COVID-19 pandemic in Keramasan Village, Kertapati District, Palembang City. This study uses a survey method by conducting in-depth interviews with a number of rice farmer households affected by the COVID-19 pandemic with a total of 30 respondents and taken purposively. The results of the study related to the social conditions of rice farmers on sub-optimal land in Keramasan Village include age, gender, educational background, number of family members, farming experience, and the distance between the location of the farm and the farmer's residence. The adaptation strategy carried out by some rice farming households in Keramasan Village during the pandemic period included physical, social, and economic strategies. Physical strategies include always wearing a mask when traveling to the city, taking a shower immediately after returning from activities (work), reducing mobility to the city, providing handwashing and soap in front of the house, not selling crops to collectors who come from outside, join the vaccination program. The social strategies carried out include reducing gathering activities, delaying or not holding large-scale celebration events, not doing halal bil halal as usual during Eid, and always monitoring the development of information about the COVID-19 pandemic in the mass media. Economic strategies undertaken include increasing income from work outside of farming, reducing household expenditures, increasing farm productivity, and increasing the percentage of farm produce for own consumption compared to the amount sold.